The Use of Fluorescence Spectra for the Detection of Scab and Rot in Fruit and Vegetable Crops - Sarimov, Ruslan M.; Lednev, Vasily N.; Sibirev, Alexey V.; Gudkov, Sergey V. (Frontiers in Physics, 2021)
Using Fluorescence Spectrometer Lumina, fluorescence spectra of surface slices of apples and potatoes were measured. Some of the samples were healthy, some were infected: apples had scabs, potatoes had rot and mechanical damage. For apples, two zones were found where the emission spectra of healthy and scab-affected samples differed significantly from each other. This is the region of 400–450 nm with excitation of 300–350 nm, as well as the region of 680–750 nm with excitation of 400–450 nm. For potatoes, the differences between a healthy and rot-affected sample were found only in the region of 400–450 nm with excitation at 300–350 nm. The found differences are clearly manifested in the correlation coefficients between the spectra - the minimum correlation coefficient for healthy apples and scab at 450 nm excitation r = 0.51. Also, healthy and diseased samples are well separated using principal component analysis (PCA). The revealed differences in the fluorescence spectra can be used for the detection and separation of diseased and healthy fruits and vegetables.